A Study on Management of Paediatric Empyema Cases: Clinical Study - Sudhakar Hegade; Sandeep Biradar (Asian Journal of Clinical Pediatrics and Neonatology, 2019)
Background: Empyema thoracis is a condition in which pus and fluid from infected tissue collects in the pleural cavity. Childhood empyema is an important complication of bacterial pneumonia. The incidence of empyema is increasing worldwide. Despite being recognized since the ancient times, the appropriate management of paediatric empyema thoracis remains controversial. Subjects and Methods: 50 suspected cases of empyema after admission had a detailed history taking as per the proforma, with emphasis on duration of symptoms, previous medication, contact history of tuberculosis and course of illness before admission. Result: In the present study, 21/50(42%) were managed with ICD and antibiotics. Another 21 cases (42%) were managed by ICD with fibrinolytics. Eight cases required thoracostomy and decortication due to poor lung expansion with persisting fever and developed multiple loculations after initial mode of treatment. Amount of pus drained was 700- 1000 ml. The time taken for fever to subside ranged from 4-12 days. Conclusion: Emphasis should be laid on minimizing the duration of hospital stay to bring down expenditure, psychological stress and more importantly nosocomial infections due to multidrug resistant organisms.